Unspoken Rome: absence in Latin literature and its reception - Geue, Tom; Giusti, Elena (Cambridge University Press, 2021)
Latin literature is a hotbed of holes and erasures. Its sensitivity to politics leaves it ripe for repression of all sorts of names, places and historical events, while its dense allusivity appears to hide interpretative clues in a network of texts that only the reader's consciousness can make present. This volume showcases innovative approaches to the field of Latin literature, all of which are refracted through this prism of absence, which functions as a fundamental generative force both for the hermeneutics and the ongoing literary aftermath of these texts. Reviewing and working with various influential approaches to textual absence, the contributors to Unspoken Rome treat these texts as silent types, listening out for what they do not say, and how they do not speak, whilst also tracing the ill-defined borders within which scholars and modern authors are legitimized to fill in the silences around which they are built.